2013
DOI: 10.1371/journal.pone.0055891
|View full text |Cite
|
Sign up to set email alerts
|

A High Throughput Genotyping Approach Reveals Distinctive Autosomal Genetic Signatures for European and Near Eastern Wild Boar

Abstract: The lack of a Near Eastern genetic signature in modern European porcine breeds indicates that, although domestic pigs from the Fertile Crescent entered Europe during the Neolithic, they were completely replaced by their European counterparts in a short window of time. Whilst the absence of such genetic signature has been convincingly demonstrated at the mitochondrial level, variation at the autosomal genomes of European and Near Eastern Sus scrofa has not been compared yet. Herewith, we have explored the genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 41 publications
(66 reference statements)
5
28
0
Order By: Relevance
“…about their complete mtDNA genome diversity Kijas & Andersson, 2001;Ni et al, 2018;Tan et al, 2018) According to Maselli et al (2016), the proportion of "Asian" haplotypes in Southern Italy and Sardinia was about 9%. Manunza et al (2013) based on the analysis of autosomal SNPs also suggested the scenario of migration from Trans-Caucasus region and Western Asia to Western Europe.…”
Section: Discussionmentioning
confidence: 99%
“…about their complete mtDNA genome diversity Kijas & Andersson, 2001;Ni et al, 2018;Tan et al, 2018) According to Maselli et al (2016), the proportion of "Asian" haplotypes in Southern Italy and Sardinia was about 9%. Manunza et al (2013) based on the analysis of autosomal SNPs also suggested the scenario of migration from Trans-Caucasus region and Western Asia to Western Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies (Larson et al, 2005;Ramírez et al, 2009) have highlighted that Near Eastern wild boar harbour mitochondrial haplotypes that are not present in modern European pig breeds (Figure 2). High-throughput analysis of the autosomal genomes of a limited number of pig and wild boar populations also demonstrated this marked genetic divergence between Near East and European Sus scrofa (Manunza et al, 2013). Moreover, European pigs and wild boars share mitochondrial haplotypes (Larson et al, 2005), a feature that would suggest that Europe was a primary domestication centre for pigs.…”
Section: The Fertile Crescent and China As The Main Centres Of Pig Domentioning
confidence: 89%
“…In fact, variability is higher in European domestic pigs (Bosse et al, 2012) mainly due to the intense admixture with Asian pigs and the selection of advantageous Asian mutations that has occurred in these lineages (Ojeda et al, 2011). In addition, historical admixture with wild boars may have also had a role until a few hundred years ago (White, 2011;Goedbloed et al, 2013;Manunza et al, 2013). Amaral et al (2011) observed a positive correlation between the level of variability and recombination (also observed in Badke et al, 2012;Bosse et al, 2012 andEsteve-Codina et al, 2013), suggesting that selection (positive or negative) has an active role in shaping the variability of Sus scrofa and that interference among genomic positions has an impact on variability.…”
Section: How Does (And Did) the Pig Genome Evolve Under Domestication?mentioning
confidence: 99%
“…Their use is also becoming feasible because of the lower genotyping costs, for example, of the Porcine SNP60 Bead-array (Ramos et al, 2009) that has recently been used for comparative studies between European pig breeds (Manunza et al, 2013;BurgosPaz et al, 2013;Herrero-Medrano et al, 2014). However, there is a well-known ascertainment bias implicit when SNP chips are used in cattle and other livestock species (Albrechtsen et al, 2010;Lachance and Tishkoff, 2013).…”
Section: Discussionmentioning
confidence: 99%